PROVING AS AN HEIR WITH A NOTARIAL DEED - Ayu Rahmawati, Shinta; Prasetyo, Mujiono Hafidh (Awang Long Law Review, 2024)
Proof that every citizen has the civil right to an heir, to be able to elimanate discrimination in formal form and officials/institutions that make evidence of an heir to the state and the people of Indonesia. The purpose of this journal article was to know how an heir was show to the notary deed (in the form of certificate of inheritance). The method of research used in compiling this journal article is normatif juridical law. The result in this journal study is that there is discrimination within a rule of law in proving as an heir and what is required of the only institution or official who is authorized to produce evidence as an heir.